Assessing variability in neurointerventional practice patterns for acute ischemic stroke. (12th December 2012) - Mehta, Brijesh; Leslie-Mazwi, Thabele M; Chandra, Ronil V; Chaudhry, Zeshan A; Rabinov, James D; Hirsch, Joshua A; Schwamm, Lee H; Rost, Natalia S; Yoo, Albert J
Abstract : Background: Intra-arterial therapy (IAT) is increasingly used to treat patients with acute stroke with large vessel occlusions. There are minimal data and guidelines for treatment indications and performance standards. We aimed to gain a better understanding of real-world practice patterns for IAT. Methods: An internet-based survey was launched to address six specific areas of IAT: practice setting, operator background, operational protocols, quality/safety, decision-making and treatment strategies. The survey invitation was distributed to members of multiple neurointerventional societies. Results: Responses from 140 neurointerventionalists worldwide were analyzed. The median annual volume of IAT cases per institution was 40, and the median neurointerventional group size was three staff members. Independent predictors of case volume were presence of comprehensive stroke services and telestroke capability. The median minimum National Institutes of Health Stroke Scale score for treatment consideration was 8, although 60% of respondents reported no minimum score cut-off. There was no strict time window from symptom onset to treatment among 41% of respondents for anterior circulation strokes and among 56% for posterior circulation strokes, instead basing treatment decisions on clinical and imaging findings. Despite the emphasis on imaging-based selection, there was pronounced variability in the criteria used. Only 27% used one imaging approach exclusively. IAT following full- or partial-dose intravenous tissue plasminogen activator was performed by 89%. Mechanical devices were the predominant first-line therapy, but specific device usage depended on practice location. Approximately half preferred conscious sedation during IAT. Conclusions: This survey illustrates significant variation among neurointerventionalists in the real-world use of IAT. Our findings highlight the need for evidence-based practice guidelines.